Experiences of hospital allied health professionals in collaborative student research projects: a qualitative study - Rebecca L. Angus; H. Laetitia Hattingh; Kelly A. Weir (BMC, 2022)
Abstract Background Active engagement in research by healthcare organisations and clinicians is associated with improvements in healthcare performance. Barriers to research engagement by clinician allied health (AH) professionals include competing priorities from high clinical workloads, lack of research skills and confidence, and lack of supportive research relationships. Collaboration with universities on joint clinical research projects is well recognised as a means of building health service research capacity. Research projects undertaken by students as part of their qualifying degree represent one such opportunity. However, there are few reports evaluating these collaborations from the health service perspective. Methods A qualitative study using semi-structured interviews and thematic analysis to explore the experiences of AH professionals in the co-supervision of students completing research placements as part of their professional degree course. Results Fourteen health service employees from six allied health disciplines described collaborations on research projects with 24 students from four different universities. Student placements and projects varied widely in length of placement, extent of collaboration, supervision structure and study design. Three overarching themes were identified in the AH professional co-supervision experience: 1) Professional growth; 2) Mismatch with expectations; and 3) Focus on the student. Project outcomes were categorised from the health system perspective. These were 1) Healthcare performance improvements, including local increases in staff clinical practice knowledge and wider contributions to the evidence base; 2) Research capacity gains within the health service, including research knowledge and skill development, collaborative linkages and opportunity for future research; and 3) Staff-centred outcomes including increased job satisfaction. Conclusions This study demonstrates the potential for AH professional supervision of students on research placements to contribute to healthcare performance improvements and research capacity gains within health services, alongside providing personal benefits for the AH professionals involved. Early consultation with a health service-employed research specialist may support health professional and student learning, team collaboration and project coordination for these student projects.